Asymptotic stability of nonlinear integrodifferential equation - Jackreece, Prebo; Aniaku, Stephen (International Journal of Applied Mathematical Research, 2018)
The investigation of stability for nonlinear dynamical system often related to the construction of Lyapunov functionals. We employ Lyapunov functionals to the system of nonlinear Volterra integro-differential equations of the form Â and obtain conditions for the asymptotic stability of the zero solution. Also, we give examples to illustrate the obtained results.